Boosting Student Mental: The Impact of Siswa Tangguh Training on Student Mental Toughness - Siti Indah Julianty; Desvi Yanti Mukhtar; Sri Supriyanti (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This study aims to evaluate the effectiveness of the Siswa Tangguh Training in improving students' mental toughness. The background of this research stems from the importance of mental toughness in supporting academic success and psychological well-being of students. This training uses the Siswa Tangguh Training Module (Mukhtar et al., 2022), developed based on the theory of Clough et al. (2002) on mental toughness. The module includes building aspirations, self-recognition, creating a positive learning atmosphere, coping with stress, and teamwork. The training was conducted in three sessions, each lasting 1.5-2 hours. Activities included material delivery, discussions, assignments, reviews, presentations, watching videos on bullying, and teamwork games. This study employed a quasi-experimental design with 36 students divided into two groups: experimental and control. Results showed that the Siswa Tangguh Training significantly improved students' mental toughness by 60.5%, with the remaining 39.5% influenced by other factors outside the research model. The implications of this study highlight the importance of programs like Siswa Tangguh in the school curriculum to support the development of students' mental toughness. The findings also suggest that schools and educational institutions consider implementing similar training modules to enhance students' mental capacity in facing academic and everyday challenges. Thus, this study contributes to the literature on psychological interventions in educational settings and provides practical guidance for curriculum developers and educational practitioners in enhancing students' mental toughness.Penelitian ini bertujuan untuk mengevaluasi keefektifan Pelatihan Siswa Tangguh dalam meningkatkan ketangguhan mental siswa. Latar belakang penelitian ini berangkat dari pentingnya ketangguhan mental dalam mendukung keberhasilan akademik dan kesejahteraan psikologis siswa. Pelatihan ini menggunakan Modul Pelatihan Siswa Tangguh (Mukhtar et al., 2022) yang dikembangkan berdasarkan teori Clough et al. (2002) tentang ketangguhan mental. Modul ini mencakup membangun cita-cita, mengenali diri, suasana belajar positif, coping stress, dan kerja sama. Pelatihan dilakukan dalam tiga sesi, masing-masing berlangsung 1,5-2 jam. Kegiatan meliputi penyampaian materi, diskusi, penugasan, review, presentasi, menonton video perundungan, dan permainan kerja sama. Penelitian ini menggunakan desain kuasi eksperimen dengan 36 siswa yang dibagi menjadi dua kelompok: eksperimen dan kontrol. Hasil menunjukkan bahwa Pelatihan Siswa Tangguh meningkatkan ketangguhan mental siswa sebesar 60,5%, dengan 39,5% sisanya dipengaruhi oleh faktor lain di luar model penelitian. Implikasi penelitian ini menekankan pentingnya program seperti Siswa Tangguh dalam kurikulum sekolah untuk mendukung pengembangan ketangguhan mental siswa. Hasil ini juga menyarankan agar sekolah dan lembaga pendidikan menerapkan modul pelatihan serupa untuk meningkatkan kapasitas mental siswa dalam menghadapi tantangan akademik dan kehidupan sehari-hari. Dengan demikian, penelitian ini berkontribusi pada literatur tentang intervensi psikologis di lingkungan pendidikan dan memberikan panduan praktis bagi pengembang kurikulum dan praktisi pendidikan dalam meningkatkan ketangguhan mental siswa.